Bilateral Congenital Agenesis of the Long Head of the Biceps Tendon: The Beginning - Francisco Rego Costa; Cátia Esteves; Lina Melão (Case Reports in Radiology)
The biceps brachii muscle is prone to variants but absence of the long head of the biceps (LHB) tendon is an exceptionally rare anomaly. This report concerns the fourth case of bilateral congenital absence of the LHB tendon and presents the ultrasonography (US) and magnetic resonance (MR) findings. Our case has the peculiarity of being the first in which bilateral LHB tendon agenesis is not associated with rotator cuff or labral tears.